Live in new normal. Space envision under post-pandemic - Huihong Zhai; Jiayi Fan (Anuari d’Arquitectura i Societat)
The arrival of the pandemic changed the peaceful lives of human beings, with many things that were taken for granted becoming difficult to do or prohibited. It redefined the relationship between safety and danger, private and public, and changed people's daily lives and habits. But while the pandemic brought negative aspects such as illness, panic, injury, and isolation, it also prompted more communication and understanding among people, pushing people to use a variety of approaches to integrate into this new public environment with protection for each individual and to find appropriate modes of getting along to explore the boundaries and transformations of the space. Under the rules and policies of segregation, a new consensus is gradually emerging in society. Distance is becoming a non-two-dimensional label, but a two-way transformation between psychological separation and physical isolation which are opposite but inter-flowing. How to define private and public space in the new living model, to realize communication and balance is the main topic of this project.